2020
DOI: 10.1136/rmdopen-2020-001242
|View full text |Cite
|
Sign up to set email alerts
|

Earlier is better when treating rheumatoid arthritis: but can we detect a window of opportunity?

Abstract: ObjectivesThe window of opportunity (WOO) hypothesis suggests a limited time frame to stop rheumatoid arthritis (RA). We hypothesised that a WOO could either be represented by a hyperbolic (‘curved’) decline in the chance to achieve the outcome sustained drug-free remission (sDFR) over time, after which achieving sDFR is not possible anymore, or by a more gradual linear decline approaching zero chance to achieve sDFR.MethodsPatients with RA (symptom duration <2 years) were included from two randomised trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…A leading model to conceptualize the benefit of early aggressive arthritis therapy in RA is the "window of opportunity hypothesis", which postulates that effective early therapy induces a durable change in natural history by interrupting an autoimmune response that is not yet well established (19). Findings of clinical trials have suggested benefits to early intervention in terms of the prevention of structural injury and, to a much more modest extent, the achievement of drug-free remission, although a specific timeframe for intervention has proven difficult to define (20)(21)(22). Our data do not directly address whether such a window of opportunity exists, but do identify an important complementary principle that we term the joint accumulation hypothesis (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…A leading model to conceptualize the benefit of early aggressive arthritis therapy in RA is the "window of opportunity hypothesis", which postulates that effective early therapy induces a durable change in natural history by interrupting an autoimmune response that is not yet well established (19). Findings of clinical trials have suggested benefits to early intervention in terms of the prevention of structural injury and, to a much more modest extent, the achievement of drug-free remission, although a specific timeframe for intervention has proven difficult to define (20)(21)(22). Our data do not directly address whether such a window of opportunity exists, but do identify an important complementary principle that we term the joint accumulation hypothesis (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the cumulative effect of such sequential treatment could contribute to determining the overall efficacy of biologic agents. On the other hand, we might speculate that earlier use of biologic agents after accurate patient selection might result in higher efficacy of such medication, following the "windows of opportunity hypothesis" elaborated for rheumatoid arthritis (48), and thus in a reduced burden of disease complication. However, in absence of higher-quality studies, we had to accept open-label studies, retrospective cohorts, and case series and outline the poor quality of evidence.…”
Section: Table IIImentioning
confidence: 99%
“…While our understanding of disease pathogenesis has greatly improved and the number of available, effective therapeutics has significantly increased, there remains significant barriers to caring for patients with RA, and they continue to suffer from the morbidity and mortality associated with the disease. There is an urgent need to develop objective biomarkers for the early diagnosis and prompt initiation of disease-modifying therapy during the so-called "window of opportunity" (3)(4)(5)(6). Additionally, clinicians need tests to help accurately assess disease activity or treatment targets in order to adjust therapy appropriately.…”
Section: Introductionmentioning
confidence: 99%